Engineering design process / Yousef Haik, Sangarappillai Sivaloganathan, Tamer Shahin - Haik, Yousef 1963-; Sivaloganathan, S. (Sangarappillai); Shahin, T. M. M. (Cengage Learning, 2018)
This third edition outlines the engineering design process in five basic stages -- requirements, product concept, solution concept, embodiment design, and detailed design. The authors take a unique approach, distinctively describing how these five stages can be seamlessly integrated. The book illustrates how the design methods can work together coherently while supporting exercises and labs to help designers efficiently navigate the design process. The book leads the beginner designer from the basics of design with very simple tasks -- the first lab involves designing a sandwich -- all the way through more complex design needs. This effective approach to the design model equips students with the skills to apply engineering design concepts not only to conventional engineering problems, but also for other design problems.